Walory edukacyjne i biblioterapeutyczne wybranej literatury górskiej i podróżniczej w kształtowaniu odporności psychofizycznej młodego człowieka (działania warsztatowe) = Educational and bibliotherapy valors of selected mountain and traveller literature in process of developing young men psyhophisical resistance (workschop activity) - Łupicka-Szczęśnik, Dagmara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Mountain and traveller activity in wide understanding of these subjects have been of interest for many years, inspiring many reserachers and put into analisis fields of such a scientic disciplines as psychology, sociology, medicine, geography with also some inputs from geology, antropology, bottany or physics. Human beings have always been attracted by unknown, not typical, difficult, virgin to explore, or unquenchable things. Taking for account our country geopolitical situation after 1989 it has been noted an unprecedential progress in numbers of so different sorts of trips with possibility to reach spots available for many years only for very few.
Keywords: biblioterapia; odporność psychiczna; literatura górska i podróżnicza; rozwój osobisty; bibliotherapy; mental resilience; mountain and traveller literature; personal development